Adapting Brief CBT-I for Depressed Adolescents: A Case Illustration of the Sleeping Better Program. Issue 3 (August 2020) - Orchard, Faith; Pass, Laura; Chessell, Chloe; Moody, Alice; Ellis, Jason; Reynolds, Shirley
Abstract: Disturbed sleep is a common symptom of depression in adolescents, but this symptom is not often targeted in psychological therapies for depression. Although the causal relationship between sleep and depression is unclear, there is increasing evidence that in adults, Cognitive Behavioral Therapy for Insomnia (CBT-I) improves sleep problems and reduces symptoms of depression; however, there has been little investigation of using this approach with adolescents. This article describes the adaptation of brief CBT-I for adolescents with depression. A single case study is reported to illustrate the use of the Sleeping Better program. Adaptations for adolescents include increased emphasis on engagement of the young person and the inclusion of parents in treatment. The treatment program was acceptable to the adolescent and parent, and treatment outcome, as indicated by sleep diaries and standardized measures of depression and anxiety, was positive. Further evaluation of the Sleeping Better program is needed to establish if it is an effective low-intensity intervention for sleep problems in adolescents who have depression or anxiety. Highlights: This case example illustrates brief CBT-I with a depressed adolescent Improvements in self-reported sleep variables were observed across treatment Reports of adolescent functioning showed clinically significant improvement Adolescent and parent acceptability of the program was demonstrated Key themes and practical challenges of the Sleeping Better program are discussed